2005
DOI: 10.1051/agro:2005009
|View full text |Cite
|
Sign up to set email alerts
|

Biofiltration onto pine bark for the treatment of water contaminated with atrazine: influence of sorbent on Pseudomonas sp. strain adp

Abstract: To cite this version:Sophie Gendrault, Rémy Bayard, Rémy Gourdon. Biofiltration onto pine bark for the treatment of water contaminated with atrazine: influence of sorbent on Pseudomonas sp. strain adp. Agronomy for Sustainable Development, Springer Verlag/EDP Sciences/ INRA, 2005, 25 (2), pp.317-321. hal-00886280 317 Agron. Sustain. Dev. 25 (2005) 317-321Abstract -A combination of adsorption and biodegradation processes was studied as a potential for the treatment of water contaminated with atrazine. Pine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Gendrault et al (2005) observed high adsorption of atrazine onto pine bark. In more general attempts positive correlation of atrazine adsorption and organic content in soils were found (Boivin et al, 2005;Spongberg and Ganglian, 2000), whereas no similar effect is known for bentazone.…”
Section: Substrate Selectionmentioning
confidence: 93%
See 1 more Smart Citation
“…Gendrault et al (2005) observed high adsorption of atrazine onto pine bark. In more general attempts positive correlation of atrazine adsorption and organic content in soils were found (Boivin et al, 2005;Spongberg and Ganglian, 2000), whereas no similar effect is known for bentazone.…”
Section: Substrate Selectionmentioning
confidence: 93%
“…Gendrault et al (2005) found that degradation of atrazine in bark extract by isolated Pseudomonas sp. strain adp (facultative denitifier) was admittedly reduced from 75 to 50% by irreversible sorption on fine bark particles (<2 mm) but not stopped.…”
Section: Behavior Of Bentazone and Atrazine In Organic Materialsmentioning
confidence: 99%
“…In addition they also provide suitable growth media for microorganisms, which has been reported to be useful for the biodegradation of some pollutants [308,309].…”
Section: Industrial and Agricultural Wastes And By-productsmentioning
confidence: 99%
“…5). Pine bark like other biosorbents is able to retain various types of organic and inorganic pollution [47][48][49] . The bark also acts as a natural biofilter for solid particles 48 , thus contributes to the retention of microalgae biomass and wastewater treatment.…”
Section: +42mentioning
confidence: 99%